Clinical Efficiency of different types of active and passive self-ligating 0.22 slot brackets - Alshaer, Abdallah M.A. (My University, 2015)
Bu çalışmanın amacı; lateral sefalometrikradyografiler ve ortodontik dijital modelleri kullanarak, aktif ve pasif kapaklı 0,22 slot braketlerin klinik etkinliklerinin karşılaştırılması ve toplam tedavi sürelerinin değerlendirilmesidir. Gereç ve Yöntem: Damon Q pasif kapaklı braket (Ormco Corporation Company, Glendora, California,USA) kullanılan 14 hasta ve Smile aktif kapaklı braket (Forestadent, Pforzeim, Germany) kullanılan 14 hasta bu çalışma için seçildi ve pasif kapaklı beaketlerdeDamon ark telleri (Damon arch shape, Ormco) kullanılırken, aktif kapaklı braketlerde Euro-Smile formunda ark telleri kullanıldı. Her iki grupta da geniş kapsamlı ortodontik tedavi uygulandı. Kayıtlar her iki grupiçin; tedavi başlangıcında (T0), 0,014'' Copper NiTi teller takıldıktan sonra ve seviyeleme tamamlandıktan ve 0,019*0,025'' çelik tellere geçildikten sonra alındı. Bulgular: Her iki grupta da; dudak projeksiyonu, üst ve alt keser diş açıları (p>0,05), interkanin, interpremolar, intermolar mesafeler artmıştır (p>0,05). Sonuçlar: Bulgular değerlendirildiğinde; Smile braket sisteminin, Damon braket sistemine göre daha hızlı bir tedavi süresine sahip olduğu, fakat tedavi etkileri ve klinik etkinliklerinin benzer olduğu söylenebilir. Anahtar Sözcükler: Kapaklı Braket, Lateral Sefalometrik Radyografi, Ortodontik Dijital Model.

Aim: The aim of this study is to compare the clinical efficiency of the different types of active and passive self-ligating 0,22 slot brackets using lateral cephalometric radiographs, orthodontic digital models and to evaluate their clinical efficiency over time. Material and Methods: 14 patients with Damon Q passive self-ligating brackets (Ormco Corporation Company, Glendora, California, USA) and 14 patients with Smile active self-ligating brackets (Forestadent, Pforzeim, Germany) were selected for the study and Damon arch wires (Damon arch shape, Ormco) were used in the passive self-ligating brackets whereas Euro-Smile form arch wires were placed in the active self-ligating brackets. Comprehensive orthodontic treatment was done in both the Smile and the Damon Q group. Records were taken initially at the beginning of treatment (T0), then after placing 0.014 Copper NiTi wires (T1) and then two months later after switching to rectangular 0.019x0.025 Stainless–steel wires (T2) for each group. Results: Lip projections, upper and lower incisor inclinations (p>0.05), inter-canine, inter-premolar, inter-molar distances are increased in both groups (p>0.05). Conclusion: According to the results derived from the study, the Smile bracket system has a shorter treatment time than the Damon bracket system but the treatment effects and the clinical efficiency for both the bracket systems are similar. Key words: Self-ligating brackets, lateral cephalometric radiographs, Orthodontic digital models.
Keywords: Ağız Sağlığı; Diş Hekimliği, Endodonti